Implementasi Kepemimpinan Transformational Pada Lembaga Pendidikan Islam - Yayuk Zulaikah; Achmad Patoni; Binti Maunah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The purpose of writing this journal is to determine the implementation of transformative leadership in Islamic educational institutions, which is an extension of charismatic leadership, leaders create a vision and environment that motivates employees to achieve beyond expectations. Transformative leadership, employees feel trust, admiration, loyalty and respect for their leadership, so they are motivated to do more than what is expected of them. In fact, it often goes beyond what they thought they could do. This research uses a type of library research. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that transformational leadership is leadership possessed by managers or leaders whose abilities are not general and are translated through the ability to realize missions, encourage members to learn, and be able to provide inspiration to subordinates regarding various things that need to be known and done. The implementation of transformational leadership refers to the 4 basic principles of transformational leadership, namely idealized influence (ideal influence and charisma). The head of the madrasah is open to interaction and two-way communication that requires each other, respects each other, accepts input, suggestions and innovative ideas from the leadership elements below him. Become a role model and work with high enthusiasm, discipline, loyalty, and hard work. Build commitment during official meetings and sign madrasa integrity facts. Providing opportunities and support for teachers and education staff to take part in webinars, training, training and bringing in speakers from outside the madrasah. Inspiration Motivation (motivational inspiration) providing motivation from the head of the madrasah directly through official meetings, discussion forums, meetings, indirectly providing words of encouragement and appreciation through electronic media. Providing rewards for teachers who excel.